1992
DOI: 10.1177/0003489492101s1004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nasopharyngeal Colonization of Hemophilus Influenzae by Oral Immunization

Abstract: Nontypeable Hemophilus influenzae organisms were inoculated into the nasopharynx of BALB/c mice immunized by oral administration of formalin-killed bacteria. Salivary antibodies and the colonization of H influenzae in the nasopharynx were investigated in order to clarify the effect of oral immunization. Salivary immunoglobulin A antibody titers against H influenzae were significantly increased by oral immunization, but salivary immunoglobulin G antibody titers were not. The bacteria inoculated into the nasopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Kurono et al showed that oral vaccination of mice caused rapid elimination of nontypeable H. influenza organisms inoculated into the nasopharynx. 23 Adegbola et al showed that vaccination with a H. influenza type b conjugate vaccine reduces oropharyngeal carriage of H. influenza type b among Gambian children. 24 Barbour et al, on the other hand, found that giving conjugate vaccine to children carrying Hib does not rapidly terminate carriage.…”
Section: Discussionmentioning
confidence: 99%
“…Kurono et al showed that oral vaccination of mice caused rapid elimination of nontypeable H. influenza organisms inoculated into the nasopharynx. 23 Adegbola et al showed that vaccination with a H. influenza type b conjugate vaccine reduces oropharyngeal carriage of H. influenza type b among Gambian children. 24 Barbour et al, on the other hand, found that giving conjugate vaccine to children carrying Hib does not rapidly terminate carriage.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, mice have been used to study OM because of the commercial availability of immunologic probes (Gu et al, 1998; Gu et al, 1996; Johnson et al, 1997; Klingman and Murphy, 1994; Krekorian et al, 1990; Kyd et al, 1999; Murphy et al, 1999). Non-genetic mouse models of OM have been generated in approximately 100 studies, of which over 30% used the BALB/c inbred strain (Chen et al, 1996; Gu et al, 1995; Hotomi et al, 2002; Ichimiya et al, 1999; Kataoka et al, 1991; Klingman and Murphy, 1994; Krekorian et al, 1991; Krekorian et al, 1990; Kurono et al, 1992; Kyd et al, 1999; Murphy et al, 1999; Ryan et al, 2006; Sarwar et al, 1992; Ward et al, 1976; Watanabe et al, 2001; MacArthur et al, 2006a). Mice have also been inoculated with bacteria or bacterial cell-wall antigens to induce immunity for studies of pathogen–host interactions (Gu et al, 1998; Gu et al, 1996; Holmes et al, 2001; Hotomi et al, 1998; Klingman and Murphy, 1994; Kodama et al, 2000; Krekorian et al, 1991; Krekorian et al, 1990; Murphy et al, 1999; Ryan et al, 2006; Sarwar et al, 1992), or with attenuated bacterial strains to seek broad (mucosal and systemic) immune protection (Roche et al, 2007).…”
Section: Mouse Models For Induced Ommentioning
confidence: 99%
“…Furthermore, mice immunized p.0. with liposomes containing inactivated NTHi not only develop high concentrations of salivary anti-NTHi IgA antibodies but also have decreased NTHi colonization in the nasopharynx (24). Our study revealed increased salivary IgA antibodies to protein D after p.0.…”
mentioning
confidence: 49%
“…Per oral (p.0.) immunization with antigen elicits S-IgA antibodies in the gut and in the respiratory mucosa (lungs and saliva) of mice and humans (3,6,10,15,24), but it is not yet clear whether immunization via these routes induces antibodies in the middle ear.…”
mentioning
confidence: 99%